Disorders of oral narrative connectivity in adults diagnosed with schizophrenia: a scoping review - Malina, Urszula Adrianna; Dębski, Robert (Logopedia Silesiana, 2023)
Deficits in discourse production are a characteristic feature of the language of individuals diagnosed with schizophrenia. A large body of research concerns the connectivity of oral narratives produced by such individuals. With the International Classification of Functioning, Disability and Health (ICF) (WHO 2001) becoming a pivotal framework in speech-language pathology clinical practice and research, continuing systematic research of this area seems to be of prime importance. Using the PRISMA-ScR methodology, a scoping review was conducted to examine the current state of knowledge on the cohesion and coherence of oral narratives in schizophrenia and to determine the main themes present in the international literature. The direct motivation for the present scoping review was to determine the dominant themes in the subject literature to plan further research using Polish language data. A thematic content analysis of the information extracted from the literature identified three themes described in the report: 1) description and classification of oral narrative connectivity deficits, 2) sources of oral narrative connectivity deficits, and 3) comparison of oral narrative connectivity disorders in schizophrenia and other diseases.